A study of wastewater discharge from electroplating factories - Lee, C. K.; Low, K. S. (Universiti Pertanian Malaysia, 1980)
There are some fifteen electroplating factories lIT Kuala Lumpur and Klang area, specializing in various forms of plating, namely chromium, zinc, silver and occasionally, cadmium, Almost all of these electroplating factories do not have any facilities for wastewater treatment. Wastewater containing cyanide and metallic ions like copper, nickel, chromium, lead, zinc, silver and others is discharged directly into drains. The presence of these pollutants can pose a health hazard to the environment if their levels exceed certain allowable limits. The present study is an attempt to determine the extent of cyanide and metal pollution in the wastewater of a typical electroplating factory without wastewater treatment and to compare the quality of its wastewater with another with treatment facilities